DEVELOPMENT OF CHILDREN’S COGNITIVE ACTIVITY IN THE SYSTEM OF PRESCHOOL AND PRIMARY EDUCATION: CONTEMPORARY METHODOLOGICAL APPROACHES (World Bulletin of Education and Learning, 2025)
This study explores the development of children’s cognitive activity within the integrated system of preschool and primary education, emphasizing contemporary methodological approaches relevant to modern pedagogical practice. Cognitive activity is understood as a complex, multifaceted process that includes curiosity, motivation, thinking, problem-solving, and the ability to independently acquire and apply knowledge. In the context of educational continuity between preschool and primary levels, the development of cognitive activity is regarded as a key condition for successful learning, adaptation, and long-term academic achievement. The relevance of the study is обусловлена the growing demand for learner-centered, competence-based education that supports children’s intellectual initiative from early childhood. The research analyzes theoretical foundations of cognitive development, drawing on constructivist, activity-based, and socio-cultural pedagogical paradigms. Particular attention is given to modern methodological approaches such as play-based learning, inquiry-based activities, problem-solving tasks, integrated learning, and the use of digital educational tools. The study highlights how these approaches contribute to sustaining children’s natural curiosity while gradually forming structured cognitive skills required in primary education. The paper also considers the role of teachers in creating pedagogical conditions that stimulate cognitive engagement, including the organization of the learning environment, the selection of age-appropriate methods, and the encouragement of independent thinking. The findings emphasize the importance of continuity between preschool and primary education in ensuring the consistent development of cognitive activity. The study concludes that the systematic application of contemporary methodologies enhances children’s cognitive readiness for school and supports their holistic intellectual development.
Keywords: Cognitive activity, preschool education, primary education, learning motivation, pedagogical methods, cognitive development, educational continuity.